Building productive pedagogical management on the basis of revealing the model of student’s learning activity - Kanashevich, Tatiana N. (University Pedagogical Journal, 2023)
The solution of the problem of organisation of productive pedagogical management of students’ learning activity is considered through understanding of its structure and variety of models. The peculiarities of students’ learning behaviour implementing different models are revealed. The typology of such models is presented and scientifically substantiated. The diagnostic toolkit is characterised and the analysis of the research work results is given.